A new program to prevent primary school absenteeism: Results of a pilot study in five schools. (November 2017) - Cook, Philip J.; Dodge, Kenneth A.; Gifford, Elizabeth J.; Schulting, Amy B.
Abstract: Frequent absences in the primary grades are associated with school disengagement, academic failure, and eventual dropout. The Early Truancy Prevention Project (ETPP) was designed to improve attendance of primary-grade children by facilitating communication between teachers and parents and giving the teachers the lead role in intervening with students when attendance problems emerge. In 2013–14, the current version of ETPP was implemented in 20 classrooms in five high-poverty public elementary schools, with 21 other classrooms in the same schools serving as controls. Our analysis of attendance data indicated that ETPP significantly reduced the prevalence of absenteeism without excessively burdening teachers. Teachers reported improved communication between parents and teachers and had a positive assessment of the effects of specific program elements. Highlights: The Early Truancy Prevention Program was piloted in 40 1st and 2nd grade classrooms. The program reduced the prevalence of frequent absences by about 10%. ETTP is the first program for younger students to have demonstrated effectiveness. ETPP places teachers at the helm and aims to improve parent-teacher communication. "Treatment" group teachers reported satisfaction with the intervention components.